Anomali Perlindungan Kebebasan Beragama dan Berkeyakinan di Mahkamah Agung - Heryansyah, Despan; Sahid Hadi (Fakultas Hukum Universitas Islam Indonesia, 2024)
This study examines the considerations of the Supreme Court justices in Decision Number 17P/HUM/2021. Through the judicial review mechanism, the decision annulled the joint decision of the Minister of Education and Culture, Minister of Home Affairs, and Minister of Religious Affairs of the Republic of Indonesia which prohibited regional governments and public schools from instructing, ordering, and requiring certain religious clothing attributes for school students. In fact, the annulled decision was issued in response to, among other things, an incident of religious-based discrimination that occurred in a public school, where the school forced non-Muslim female students to wear the hijab. Based on the provisions of human rights law on freedom of religion and belief, this study focuses on analyzing the legal considerations of the Supreme Court in Decision Number 17P/HUM/2021 and shows more contextual issues from the issuance of the decision, especially in terms of the substance and administration of court decisions. Emphasizing the anomaly in the protection of freedom of religion and belief in the Supreme Court, this doctrinal research identifies a number of structural, substantial, and technical problems in the implementation of judicial review in the Supreme Court. In specific cases such as those involving aspects of freedom of religion and belief, Decision Number 17P/HUM/2021 indicates the failure of the Supreme Court to protect and respect such freedom. Behind such failure, this study also argues that the Supreme Court favours the conservative turn in religious practices and thus poses a problem in regards to th impartiality of justices in their performance.Keywords: Anomaly, Impartiality, Freedom of Religion and Belief, Conservative Turn, Supreme Court AbstrakStudi ini menelisik pertimbangan hakim Mahkamah Agung dalam Putusan Nomor 17P/HUM/2021. Melalui mekanisme judicial review, putusan tersebut membatalkan keputusan bersama Menteri Pendidikan dan Kebudayaan, Menteri Dalam Negeri, dan Menteri Agama Republik Indonesia yang melarang pemerintah daerah dan sekolah publik untuk tidak mewajibkan, memerintahkan, dan mensyaratkan atribut berpakaian agama tertentu bagi siswa-siswi sekolah. Padahal, keputusan yang dibatalkan itu diterbitkan dalam rangka merespons, antara lain, peristiwa diskriminasi berbasis agama yang terjadi di sebuah sekolah publik, yang mana sekolah memaksa siswi non muslim untuk menggunakan jilbab. Berdasar pada ketentuan hukum hak asasi manusia tentang kebebasan beragama dan berkeyakinan, studi ini difokuskan untuk menganalisis pertimbangan hukum Mahkamah Agung dalam Putusan Nomor 17P/HUM/2021 dan menunjukkan persoalan-persoalan yang lebih kontekstual dari penerbitan putusan tersebut, terutama dari segi substansi dan administrasi putusan pengadilan. Menekankan adanya anomali perlindungan kebebasan beragama dan berkeyakinan di Mahkamah Agung, penelitian doktrinal ini mengidentifikasi sejumlah persoalan struktural, substansial, dan teknis dalam implementasi judicial revew di Mahkamah Agung. Dalam kasus-kasus spesifik seperti yang melibatkan aspek kebebasan beragama dan berkeyakinan, Putusan Nomor 17P/HUM/2021 menunjukkan kegagalan Mahkamah Agung dalam melindungi, sekaligus menghormati, kebebasan tersebut. Di balik kegagalan tersebut, studi ini juga berargumen bahwa Mahkamah Agung tengah berada dalam putaran konservatif praktik keagamaan dan memiliki problem imparsialitas hakim dalam kinerjanya.Kata Kunci: Anomali, Imparsialitas, Kebebasan Beragama dan Berkeyakinan, Putaran Konservatif, Mahkamah Agung